Lipidation of pneumococcal proteins enables activation of human antigen-presenting cells and initiation of an adaptive immune response - Paulikat, Antje D.; Schwudke, Dominik; Hammerschmidt, Sven; Voß, Franziska (Frontiers in Immunology, 2024)
Streptococcus pneumoniae remains a significant global threat, with existing vaccines having important limitations such as restricted serotype coverage and high manufacturing costs. Pneumococcal lipoproteins are emerging as promising vaccine candidates due to their surface exposure and conservation across various serotypes. While prior studies have explored their potential in mice, data in a human context and insights into the impact of the lipid moiety remain limited. In the present study, we examined the immunogenicity of two pneumococcal lipoproteins, DacB and MetQ, both in lipidated and non-lipidated versions, and evaluated their ability to activate primary human immune cells in various in vitro models. Our findings indicate that in the case of MetQ lipidation was crucial for activation of human antigen-presenting cells such as dendritic cells and macrophages, while non-lipidated DacB demonstrated an intrinsic potential to induce an innate immune response. Nevertheless, immune responses to both proteins were enhanced by lipidation. Interestingly, following stimulation of dendritic cells with DacB, LipDacB and LipMetQ, cytokine levels of IL-6 and IL-23 were significantly increased, which are implicated in triggering potentially important Th17 cell responses. Furthermore, LipDacB and LipMetQ were able to induce proliferation of CD4+ T cells indicating their potential to induce an adaptive immune response. These findings contribute valuable insights into the immunogenic properties of pneumococcal lipoproteins, emphasizing their potential role in vaccine development against pneumococcal infections.